2021
DOI: 10.1212/wnl.0000000000012109
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Biomarkers in Alzheimer Disease

Abstract: Objective:To perform a systematic review and meta-analysis to determine whether fluid and imaging astrocyte biomarkers are altered in Alzheimer's disease (AD).Methods:PubMed and Web of Science databases were searched for articles reporting fluid or imaging astrocyte biomarkers in AD. Pooled effect sizes were determined with mean differences (SMD) using the Hedge’s G method with random-effects to determine biomarker performance. Adapted questions from QUADAS-2 were applied for quality assessment. A protocol for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 70 publications
0
55
1
Order By: Relevance
“…12,13 Cerebrospinal fluid (CSF) levels have been shown to differentiate individuals with dementia from cognitively unimpaired adults. 14,15 With the use of ultrasensitive assays, GFAP levels can be detected in blood, and some recent studies have reported that circulating levels associate with poorer cognition and ADRD status. [16][17][18][19][20] Relevant to secondary prevention efforts, plasma GFAP levels have also been found to predict amyloid positivity among cognitively unimpaired adults.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Cerebrospinal fluid (CSF) levels have been shown to differentiate individuals with dementia from cognitively unimpaired adults. 14,15 With the use of ultrasensitive assays, GFAP levels can be detected in blood, and some recent studies have reported that circulating levels associate with poorer cognition and ADRD status. [16][17][18][19][20] Relevant to secondary prevention efforts, plasma GFAP levels have also been found to predict amyloid positivity among cognitively unimpaired adults.…”
Section: Introductionmentioning
confidence: 99%
“…Chitinase 3-like-1 (CHI3L1), also known as YKL-40, has been extensively studied as a cerebrospinal fluid biomarker for diseases such as Alzheimer's disease and dementia (10). As a carbohydrate-binding lectin that mediates inflammation, YKL-40 is regulated by the circadian rhythm of astrocytes and increases the deposition of beta-amyloid during the inflammatory response, thereby accelerating the pathological process of Alzheimer's disease (11).…”
Section: Introductionmentioning
confidence: 99%
“…A large range of other targets, including noradrenergic [ 159 ], mitochondrial [ 160 ] and synaptic vesicular markers [ 161 ] have been explored in AD. In recent years, imaging of activated microglia and astrocytes has attracted most interest as a research area with therapeutic potential [ 162 , 163 ]. It will likely be relevant for predicting disease progression at the MCI stage but so far has not been associated with specific AD subtypes.…”
Section: Imaging Techniquesmentioning
confidence: 99%